Achieving the win–win: targeted agronomy can increase both productivity and sustainability of the rice–wheat system - Chaki, Apurbo K.; Gaydon, Donald S.; Dalal, Ram C.; Bellotti, William D.; Gathala, Mahesh Kumar; Hossain, Akbar; Menzies, Neal W. (Springer, 2022)
Maximizing productivity of the rice–wheat (RW) system is a major challenge for achieving food security in the Eastern Gangetic Plains (EGP) of South Asia. Ideally, productivity should increase along with increasing farm profits while sustaining or enhancing the natural resource base. However, research focused on increasing the productivity and profitability of the RW system while considering long-term system sustainability is lacking from the EGP. Here, we show that using the process-based cropping system model Agricultural Production Systems sIMulator (APSIM) (earlier robustly validated in these environments), maximization of target variables (e.g. production, farm profit, water productivity) can be achieved by modifying the agronomic management currently recommended for RW farmers in the region. Our analysis demonstrates conservation agriculture-based intensification, through the addition of mungbean with modified irrigation and increased nitrogen fertilization, increases not only the system production (34%), farm profit (39%), and water productivity (54%), but also the soil organic carbon (31%) and total soil nitrogen (52%) in the 0–15 cm soil layer. In contrast, conventional tillage-based intensification increases system productivity but not sustainability. We found the ideal agronomic management varied across different environments for maximizing target variables. Our analysis illustrates the power of validated modeling tools like APSIM and has broader application for farmers globally whose production and sustainability are constrained by inefficient agronomic practices.